Citra merek, kualitas produk dan harga pengaruhnya terhadap keputusan pembelian pada produk private label (studi kasus pelanggan Alfamart Villa Muka Kuning Batam) - Rustam, Triana Ananda; Hikmah, Hikmah (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2022)
This study aims to determine how brand image, product quality and price affect purchasing decisions. The population in this study was residents of Villa Muka Kuning, Batam City who had shopped at Alfamart Villa Muka Kuning. Due to the unknown population, the sample size of 204 respondents with Jacob Cohen formula. The sampling technique used is purposive sampling.The test method uses multiple linear regression and classical assumption tests, namely normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, t-test, F test, and coefficient test (R2). The results of this study are :1) brand image,quality and price perception have a significant effect on purchase decision. (2) have a simultaneous effect on purchase decision.